Reinterpretation of Maqasid Sharia of Post Pandemic Islamic Fintech Lending Regulation in Indonesia - Hasna Mumtaza Abdullah; I Isman (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to reinterpret maqasid al-shariah, particularly hifdz al-mal and tahqiq al-maslahah, in assessing the post-pandemic regulatory framework of sharia fintech lending in Indonesia based on OJK Regulation No. 10/POJK.05/2022 and DSN–MUI Fatwa No. 117/2018. It seeks to evaluate the extent to which these regulations respond to emerging risks from the integration of artificial intelligence (AI), big data, and blockchain, while supporting sustainable financial inclusion. Methodology: Employing a qualitative normative juridical approach, this research analyzes positive law (OJK regulations, UU ITE, UU PDP) and DSN-MUI fatwas through content analysis combined with a maqasid al-shariah framework. Secondary data from statutes, fatwas, policy documents, and contemporary literature on Islamic fintech and maqasid al-shariah are systematically examined to map regulatory provisions on contracts, transparency, risk mitigation, consumer protection, and data governance. Results: The findings show that the existing framework has facilitated the growth of sharia P2P lending and supported financial inclusion and MSME empowerment, yet it remains only partially aligned with maqasid al-shariah. Gaps persist in the form of digital gharar arising from opaque AI-based scoring, potential embedded riba in risk-pricing, and vulnerabilities in personal data protection that are not fully addressed by current regulations. Applications/Originality/Value: This study offers a maqasid-based reinterpretation of sharia fintech lending regulation in the post-pandemic era by proposing regulatory ijtihad on algorithmic transparency, sharia-compliant smart contracts, and data protection standards. It contributes a conceptual model of shariah tech governance that integrates fiqh muamalah, positive law, and ethical technology principles, thereby positioning sharia fintech as a vehicle for sustainable financial inclusion and the achievement of SDGs 8 and 10.